Foreign direct investment, development and gender equity: A review of research and policy - Elissa Braunstein (United Nations Research Institute for Social Development (UNRISD), 2006)
This paper provides a summary of the empirical and policy-related literature on the multifaceted relationships between gender inequalities and foreign direct investment (FDI). The literature on gender and FDI is evaluated with reference to the broader literature on FDI and economic development, new research directions are identified, and the policy implications of managing FDI for development and gender equity are discussed. The empirical literature on the relationship between FDI and growth and development is surprisingly mixed. The paper reviews the research on the impact of FDI on investment, productivity, trade, employment, wages and working conditions, and finds few of the straightforward conclusions that the popularity of FDI as a tool for development would seem to indicate. However, despite a number of open questions and seeming contradictions, two consistent issues repeatedly arise. First, very little is understood about the dynamic impact of FDI. Even where positive correlations between FDI and investment, employment or wages appear, there is little analysis of whether and how the impact is sustained - to what extent (and how) FDI impacts the process and trajectory of development. Second, the research in which there does seem to be an emerging consensus is on the importance of the economic and policy context for FDI in determining its eventual impact. In terms of women and FDI, it is clear that foreign investment in labour-intensive, largely export-oriented industries has had a significant impact on women's work and development. While there has been a positive relationship between women's employment and FDI in semi-industrialized countries, there is mounting evidence that women either lose jobs to more highly qualified men as industries upgrade, or get pushed down the production chain into subcontracted work as competition forces firms to continually lower costs. There is likely to be some short-term improvement in women's incomes as FDI expands, but the longer-term trajectory of women's wages is less promising. In terms of gender-based wage inequality, the research on FDI is consistent with other findings that trade does not systematically narrow the gender wage gap. The nature of gender segmentation and industrial distribution - where women are concentrated in highly competitive traded sectors - and the high mobility of transnational capital are instrumental in determining the gender wage gap...
Keywords: 330